A universidade latinoamericana contra a globalização. Continuidades e inflexões de um processo: (1968 e 2011) (2017)
The aim of this article is to analyze the dynamics of globalization and technocracy in scenarios such as the higher education. The text is part of a research project that pursues to ask after two social dynamics: the first in the year 1968 and the second in 2011. The proposal is addressed not only to explain the mobilizing tensions in the middle of a Globalized panorama, but to identify the global dynamics as the constructive quality of sociabilities from the second half of the twentieth century to the present.